“V.M. Bekhterev Review of Psychiatry and Medical Psychology” — History of the First Psychiatric Journal in Russia - Yuri V. Popov; Nikolay G. Neznanov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
The article presents the historical facts oт the creation of the first psychiatric journal in Russia (1896). The organizer of the journal and its first editor-in-chief was V.M. Bekhterev. After his death in 1927, the journal was named after him. It had been published until its closure in 1930. For various reasons, some of which are discussed in the article, the journal has not been published for six decades. The organizational difficulties of registering printed materials that existed at that time are also described. Nevertheless, they were overcome, and in 1990 the USSR State Press Committee issued the Order «On the resumption of publication of the journal...». The journal received a Registration Certificate and was assigned to almost the highest group of central journals. All financing was assigned to the Leningrad branch of the publishing house «Medicine», and the journal was printed in the fabulous in modern reality figure of 20,000 copies per month.After the collapse of the USSR in 1991, this Order ceased to be valid, and the whole thing had to be started all over again. Nevertheless, the first issue of the journal was published in 1991. Its release has been expected not only in Russia, but also abroad. The first issue included a welcoming speech by the President of the World Psychiatric Association, Jorge Alberto Costa e Silva, which attracted even more attention towards the journal. In 1992, the American Psychiatric Association published an English-language digest of the journal in the United States. For some time the journal was also published in Paris (1998-2000) and in Moscow (2004-2011). Currently, the journal is published by its founder, the V.M. Bekhterev National Medical Research Center for Psychiatry and Neurology in St. Petersburg and is one of the most renowned journals in the field of psychiatry and medical psychology in Russia.